Using ecosystem approach indicators for assessing the ecological status of reef fisheries management in a marine protected area - ERNIK YULIANA; MENNOFATRIA BOER; ACHMAD FAHRUDIN; MOHAMMAD MUKHLIS KAMAL; SHINTA TRILESTARI PARDEDE (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Yuliana E, Boer M, Fahrudin A, Kamal MM, Pardede ST. 2019. Using ecosystem approach indicators for assessing the ecological status of reef fisheries management in a marine protected area. Biodiversitas 20: 1802-1810.  The purpose of this study was to assess the status of reef fisheries management in a marine protected area base on ecosystem approach indicators and to determine the tactical decisions required to improve management. The study site was in Karimunjawa National Park (KNP) Jepara, Central Java, Indonesia. Data were collected using survey and observation methods and included both primary and secondary data. Coral fish, which were the object of the study was Caesio cuning, Caesio caerulaurea, Plectropomus oligacanthus, and Parupeneus barberinus. Determination of the status of each ecosystem approach indicator was conducted using the flag model. Tactical decisions were necessary to improve the status of management indicators. The results indicated that the ecological status of reef fisheries management of KNP is at a moderate level with an achievement value of 62.75% Tactical decisions are necessary to push the ten indicators to achieve a better level. Three indicators still received a poor status, and the remaining (seven indicators) were within the moderate status. Therefore, the three indicators that need to be improved quickly are fish abundance, fishing gear modification, and fishing capacity.